Strategi Solutif Terhadap Kendala Dalam Mendukung Brand Awareness di Media Massa dan Platform Digital Pada Produk Real Estate PT. Muara Alam Indonesia - Adnyana, Agus Widhi; Listiawati, Ni Putu; Yudhiarsana, I Made Agus (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2025)
This study aims to examine the solutions implemented by PT. Muara Alam Indonesia to the obstacles that occur in supporting brand awareness of real estate products in mass media and digital platforms. The solutions implemented by PT. Muara Alam Indonesia are carried out with a psychological, informative and transparent communication approach. The method used in this study is qualitative research with a case study approach with data collection techniques using non-participant observation, semi-structured interviews and in-depth documentation of the mass media used by PT. Muara Alam Indonesia. Data analysis uses the theory of possible elaboration. The results of the study indicate that the solutions implemented by PT. Muara Alam Indonesia are by conducting morning briefings and compiling more creative digital pamphlets as a form of solution to the obstacle of using cliché sentences, disseminating complete and transparent information as a solution to audience skepticism towards real estate advertising, and always informing the audience about the project development process until completing previously stalled projects as a solution to the obstacle of the community's negative perspective on developers.